Statins and Survival in Castration-Resistant Prostate Cancer After Abiraterone or Enzalutamide: A Systematic Review - Setiawan, Encep Ivan; Danarto, Raden (Indonesian Journal of Cancer, 2026)
Background: Prostate cancer is the second most commonly diagnosed cancer in men worldwide and a leading cause of cancer-related mortality. Castration-resistant prostate cancer (CRPC) develops despite androgen deprivation therapy (ADT), often after treatment with abiraterone or enzalutamide. Statins have shown potential anticancer effects through inhibition of HMG-CoA reductase and related signaling pathways. This systematic review evaluated whether statin use improves survival and disease outcomes in patients with CRPC previously treated with abiraterone or enzalutamide.Methods: A systematic search of PubMed, ProQuest, SAGE, and Europe PMC was conducted following PRISMA and Cochrane guidelines. Studies published within the last 10 years were included if they involved adults with CRPC receiving ADT or orchiectomy and compared statin users with non-users. Risk of bias was assessed using RoB 2.0 for randomized controlled trials (RCTs) and ROBINS-I for non-randomized studies. Primary outcomes were overall survival (OS), cancer-specific survival (CSS), and prostate-specific antigen (PSA) response.Results: Eight studies (two RCTs and six retrospective cohort studies) involving 35,401 patients were included. Most studies had a low to moderate risk of bias. Results were heterogeneous. Two of four studies reported significantly improved OS among statin users, while the remaining studies found no significant association. One study showed improved CSS, and two studies reported higher PSA response rates with statin use. However, these benefits were not consistently observed throughout all studies.Conclusion: Statin use may improve survival outcomes and PSA response in patients with CRPC. However, current evidence remains